ANALISIS REKAYASA LALU LINTAS SIMPANG EMPAT MANNA KAMPUS GODEAN, JALAN YOGYAKARTA - DEMAKIJO, NGESTIHARJO, KASIHAN, BANTUL - Susanto, Nur Budi; Haryanto, Iman; Hidayat, Nursyamsu; Wiryanta; Aryaradjasa, Renno; Putri, Ferrolinna Cendykia; Sektiaji, Hutama (Jurnal Teknik Sipil dan Arsitektur, 2026)
Yogyakarta – Demakijo Road, better known as Godean Road, is a primary collector road in the Special Region of Yogyakarta that connects the city of Yogyakarta, Bantul Regency, and Sleman Regency. Along Yogyakarta – Demakijo, there are several 3-arm and 4-arm road intersections that connect to the surrounding areas. This study analyzes the traffic performance and provides engineering recommendations for the Manna Kampus Godean Four-Arm Intersection on Yogyakarta-Demakijo Road, Ngestiharjo, Kasihan, Bantul. The research was prompted by the policy of closing right-turn access via water barriers, forcing vehicles to make U-turns and creating weaving movements. The analysis method employed the 2023 Indonesian Road Capacity Manual (PKJI) to evaluate the performance of the four existing weaving sections. The results indicate that all sections suffer from a very high degree of saturation (DS), exceeding 1.5, signifying overcapacity conditions. Traffic delays were also recorded, ranging from 2.01 to 2.95 seconds/pcu. To achieve the ideal DS of ? 0.85, simulations recommend widening the weaving sections to 11-16 meters. However, a cost analysis reveals that land acquisition alone would require a minimum budget of IDR 70 billion, coupled with potential social conflicts. As an alternative, reactivating the traffic signals (APILL) could be considered but necessitates further in-depth study on vehicle movement characteristics.